Early Realignment Versus Delayed Urethroplasty in Management of Pelvic Fracture Urethral Injury: A Meta-analysis - Rama Firmanto; Gampo Alam Irdam; Irfan Wahyudi (Acta Medica Indonesiana)
Aim: this meta-analysis study will evaluate the incidence of urethral stricture as a successfull parameter in the management of PFUI through early realignment, compared with delayed urethroplasty. Long-term complications such as erectile dysfunction and incontinence on both methods will also be evaluated. Methods: online literature was sourced from Pubmed, Embase, Cochrane, and Google Scholar. The incidence of stricture was evaluated from the entire study group of ER and DU. Stricture of the urethra is diagnosed by the symptoms such as the obstruction that felt by the patient, uroflowmetry examination, and urine residual post micturition that supported by urethrography examination at regular interval. In some cases the incidence of stricture also diagnosed by urethroscopy. The patient is assessed as not having stricture when it is no longer needed to do urethral dilatation or advanced urethrotomy. The rate of incontinence was assessed subjectively from the patient’s complaints. The erectile function assessed subjectively; decreased of tumesen’s degree, reduced the duration of erection, and penetration failure diagnosed as erection dysfunction. The data were processed as dichotomy data to calculate the risk ratio using Review Manager 5.1. Results: five relevant literatures reviewed in this study. The incidence of urethral strictures are statistically significant lower in early realignment group (RR=0.70, 95% CI 0.50-0.99, P<0.05). There were no statistically significant differences between both treatment groups on the incidence of erectile dysfunction (RR=0.72, 95% CI 0.39-1.34) nor the incidence of incontinence (RR=0.74, 95% CI 0.36-1.51). Conclusion: early realignment decrease the occurrence of stricture on PFUI treatment compared to delayed urethroplasty method. Between the two methos, the complications such as erectile dysfunction and incontinence; however, there was no significant difference.